(untitled) (Revista Argentina de Musicología, 2024)
This paper proposes musical narrative analysis as a significant strategy to complement other analytical perspectives in exploring the particular expressive meanings of the work Soliloquio for oboe, by Argentine composer Gerardo Gandini. The text is organized into three parts: the first part briefly discusses the traditional categories of author, work, text, performer, and performance, and provides a formal, motivic, and pitch-class set analysis; the second part reviews perspectives and proposals for the analysis of musical narrativity; and the third part offers a narrative analysis of the work following Almén’s (2017) approach.